Understanding the Victorians - Steinbach, Susie, author.
1 online resource
Keywords: "Understanding the Victorians paints a vivid portrait of an era of dramatic change, combining broad survey with close analysis and introducing students to the critical debates on the nineteenth century taking place among historians today. The volume encompasses all of Great Britain and Ireland over the whole of the Victorian period and gives prominence to social and cultural topics alongside politics and economics and emphasises class, gender, and racial and imperial positioning as constitutive of human relations. This third edition is fully updated with new chapters on emotion and on Britain's relationship with Europe as well as added discussions of architecture, technology, and the visual arts. Attention to the current concerns and priorities of professional historians also enables readers to engage with today's historical debates. Starting with the Queen Caroline Affair in 1820 and coming up to the start of World War I in 1914, thematic chapters explore the topics of space, politics, Europe, the empire, the economy, consumption, class, leisure, gender, the monarchy, the law, arts and entertainment, sexuality, religion, and science. With a clear introduction outlining the key themes of the period, a detailed timeline, and suggestions for further reading and relevant internet resources, this is the ideal companion for all students of the nineteenth century. Discover more from Susie by exploring our forthcoming Routledge Historical resource on British Society, edited by Susie Steinbach and Martin Hewitt. Find out more about our Routledge Historical resources by visiting Link